Exploratory study cervical cancer risk factors and efficacy of screening methods - Ferolin, Maria Cecilia M. (Langkit : the Official journal of the College of Arts & Social Sciences Mindanao State University-Iligan Institute of Technology, 2012)
This study was undertaken to determine the following: (1) the prevalence of pre-malignant cervical lesions among women of reproductive ages who undergo screening using PAP smear and VIA; (2) treatment rates among women who test positive with PAP smear or VIA; (3) the sensitivity and specificity of PAP smear and VIA as performed in a local setting; (4) the frequency of occurrence of risk factors in women of reproductive ages with positive results in either PAP smear or VIA. The study was conducted in a secondary health facility. Five hundred twenty six (526) women who fulfilled the inclusion criteria were screened using both PAP smear and VIA.